The critical barrier to progress in dentine bonding with the etch-and-rinse technique - Brackett, M. G.; Li, N.; Brackett, W. W.; Sword, R. J.; Qi, Y. P.; Niu, L. N.; Pucci, C. R. [UNESP]; Dib, A.; Pashley, D. H.; Tay, F. R. (Elsevier B.V., 2011)
Objectives: The lack of durability in resin-dentine bonds led to the use of chlorhexidine as MMP-inhibitor to prevent the degradation of hybrid layers. Biomimetic remineralisation is a concept-proven approach in preventing the degradation of resin-dentine bonds. The purpose of this study is to examine the integrity of aged resin-dentine interfaces created with a nanofiller-containing etch-and-rinse adhesive after the application of these two approaches.Methods: The more established MMP-inhibition approach was examined using a parallel in vivo and in vitro ageing design to facilitate comparison with the biomimetic remineralisation approach using an in vitro ageing design. Specimens bonded without chlorhexidine exhibited extensive degradation of the hybrid layer after 12 months of in vivo ageing.Results: Dissolution of nanofillers could be seen within a water-rich zone within the adhesive layer. Although specimens bonded with chlorhexidine exhibited intact hybrid layers, water-rich regions remained in those hybrid layers and degradation of nanofillers occurred within the adhesive layer. Specimens subjected to in vitro biomimetic remineralisation followed by in vitro ageing demonstrated intrafibrillar collagen remineralisation within hybrid layers and deposition of mineral nanocrystals in nanovoids within the adhesive.Conclusions: The impact was realized by understanding the lack of an inherent mechanism to remove water from resin-dentine interfaces as the critical barrier to progress in bonding with the etch-and-rinse technique. The experimental biomimetic remineralisation strategy offers a creative solution for incorporating a progressive hydration mechanism to achieve this goal, which warrants its translation into a clinically applicable technique. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Ageing; Biomimetic remineralisation; Chlorhexidine; Degradation; Hybrid layer; Matrix metalloproteinase